STYLISTIC CHARACTERISTICS OF UZBEK AND ENGLISH OFFICIAL DOCUMENTS - Rakhmatova Mukhlisakhan Odiljan kizi (Journal of new century innovations, 2022)
Abstract: The article provides comprehensible information about formal speech texts. Also, methodological features of Uzbek official speech texts are scientifically studied.